Factores de riesgo y su relación con la morbimortalidad en neonatos atendidos en el Hospital Sagrado Corazón de Jesús. Noviembre 2023 abril 2024. - Massuth Rizzo, Juan Amauri (2024)
High morbidity and mortality in neonates represent a critical challenge in perinatal care due to the persistence of risk factors, which underlines the urgency of more coordinated and effective interventions. The general objective of the study was to determine the risk factors and their association with morbidity and mortality in neonates treated at the Sacred Heart of Jesus Hospital during the study period. The deductive method was used to examine the causes of the problem in question, as well as the logical historical method for the review of past events. Documentary reviews and surveys were also included. The samples of this study were 93 neonates treated at the Sacred Heart Hospital. de Jesús and all the nurses belonging to the neonatology area. Among the results, the predominance of male neonates, the prevalence of harmful maternal behaviors such as alcohol and drug consumption, as well as the proportion of neonates with weights outside the optimal range stand out. Geographic location and access to medical care emerge as crucial factors, along with the association between the number of prenatal checkups and the incidence of complications during pregnancy. The importance of several factors, such as maternal behaviors, medical conditions during pregnancy, childbirth, and socio-environmental factors, on the health and survival of newborns is highlighted.